PELUANG TRANSISI PADA PENENTUAN PREMI TUNGGAL BERSIH ASURANSI JIWA BERJANGKA - Muhammad Meidy Maulana; Dewi Sri Susanti; Aprida Siska Lestia (Mathematics Study Program, Faculty of Mathematics and Natural Sciences, Lambung Mangkurat, 2022)
A life insurance contract contains the amount of funds that must be paid by insured as a responsibility for a received compensation. There funds are called as premium. Payment of the premium which paid with one payment at the beginning of the contract time called as net single premium. One factor that influenced the calculation of life insurance premiums is a life probability. In general, a life probability constructed by the assumption that death only involves two conditions, life and death. Yet, there are another condition for the insured that also affect a person’s death condition which is sick. The objecktive of this research is to determine net single premium of term life insurance formula using transition probability as a life probability. The first will constructed transition from three condition which are health, sick, and death as stochastic process. Transition probability will be determined by solving Chapman Kolmogorov system differential equation. Then the probability transition that determined will be used for calculate net single premium from term life insurance. Net single premium will be determined by using expectation value of present value of benefit random variables. From this research get formula of net single premium of term life insurance contains discount function, transition probability, and force of mortality of someone.